Introducing Old Testament theology creation, covenant, and prophecy in the divine-human relationship - Bellinger, W. H. Jr. 1949- (Grand Rapids Baker Academic, a division of Baker Publishing Group, 2022)
1. Beginnings -- 2. A shape for Old Testament theology -- 3. Pentateuch -- 4. Historical books -- 5. Psalms -- 6. Wisdom -- 7. Prophecy.
"A senior scholar and teacher offers a concise, student-level theology of the Old Testament"--
Includes bibliographical references and index
Keywords: Bible -- Theology; Bible -- Criticism, interpretation, etc